Application of Novel Drugs for Corneal Cell Regeneration. (2nd May 2018) - Han, Sang Beom; Liu, Yu-Chi; Mohamed-Noriega, Karim; Mehta, Jodhbir S.
Abstract : Corneal transplantation has been the only treatment method for corneal blindness, which is the major cause of reversible blindness. However, despite the advancement of surgical techniques for corneal transplantation, demand for the surgery can never be met due to a global shortage of donor cornea. The development of bioengineering and pharmaceutical technology provided us with novel drugs and biomaterials that can be used for innovative treatment methods for corneal diseases. In this review, the authors will discuss the efficacy and safety of pharmacologic therapies, such as Rho-kinase (ROCK) inhibitors, blood-derived products, growth factors, and regenerating agent on corneal cell regeneration. The promising results of these agents suggest that these can be viable options for corneal reconstruction and visual rehabilitation.